/08/ Patricia Esquivias - Cesarco, Alejandro; Esquivias, Patricia (Galería Elba Benítez, 2025)
/08/ is an annual series of exhibitions organised by Alejandro Cesarco that take place while the gallery is closed for its summer break. This August /08/ presents an intervention by Patricia Esquivias on the gallery’s answering machine. Esquivias uses this space to host a micro-exhibition of her usual methods: pointing towards something forgotten, weaving together personal memory with public or official history, and using her voice as the narrative thread.